Nutritional content of menu for basic recruit training in military foodservice - Nurhazwani Abdullah; Nurul Aziah Ahmad; Aikal Liyani Mohd Rasdi (2014)
The study was to evaluate the nutrient content of menu provided to recruits in the Basic Recruit Training Centre, Port Dickson, Malaysia. From a 4-week cycle menu, the menu during week 3 of a 4-week cycle menu was randomly chosen to obtain average nutrient content. Nutrient content of menu was evaluated on 7 days from three main meals (breakfast, lunch, dinner) and snacks (morning and tea breaks) and was compared with the Recommended Nutrient Intakes (RNIs) of Malaysia and the military dietary recommendation for Malaysian Armed Forces, Perintah Majlis Angkatan Tentera (PMAT) to determine the nutritional adequacy of the menu for male recruits. The energy from the menu was within the range of 2772 to 2843 kcal, and met the energy recommendation of RNIs for general male aged 19 to 29 years but it did not meet the energy recommendation for recruits in training based on military dietary recommendation, PMAT. Protein from the menu has exceeded the RNIs and PMAT recommendation (17.4% to 18.3%). Fat content of the menu ex-ceeded the recommended range of 20% to 30%. Carbohydrate was not sufficiently provided by the catering within the recommended carbohydrate range of 55% to 70%. Nutrient values for vitamin A, vitamin C, iron, thiamine, riboflavin, niacin, sodium and zinc met the recommendation of RNIs (100% of RNIs). However, the levels of calcium and dietary fiber in the menu were suboptimal. Therefore, corrective action should be taken to ensure the nutrient content of menu provided is sufficient for the physical activity level of recruits during training especially from carbohydrate food sources